The Cooperatives accordance with the law and the Sociology of Work - Alcântara, Fernanda Henrique Cupertino (Organizações & Sociedade, 2014)
This article discusses the treatment given to the Cooperativism Law and the Sociology of Work, grounded on the phenomenon of productive restructuring and flexibility, with the advent of new legislation on labor cooperatives. I also approach the contributions of these research field for self-management solidarity enterprises and indicates some of the recurring themes in the literature on this subject. The paper also discusses the profile of the case law of the TST on the theme and cooperative working relationship. Last but not least, this work demonstrates how Law 12,690 of July 19, 2012, which consolidates much of the responses to the concerns present in the literature cited, is recognized as a watershed in the legal treatment given to self-managed enterprises solidarity branch work.